2010
DOI: 10.1111/j.1365-2362.2010.02384.x
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent impairment of number and angiogenic potential of adipose tissue-derived progenitor cells

Abstract: Ageing may alter the availability of adipose tissue-derived CD45(-)/CD34(+)/CD133(+) cells and their angiogenic functional capacity. Such changes may impair the use of adipose tissue as source of autologous PCs in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 34 publications
4
58
0
2
Order By: Relevance
“…While an analysis of breast tissues specimens from >180 women donors aged 16-73 did not observe an age dependent difference in stromal cell numbers or adipogenesis, increased body mass index correlated significantly with reduce cell numbers and differentiation [9]. Clinical studies examining subcutaneous adipose tissue from 12 to 52 donors have reported reduced ASC adipogenesis, angiogenesis, osteogenesis, and/or proliferative capacity as a function of advancing donor age [10][11][12]. Similarly, a detailed comparison of five different subcutaneous depots determined that ASC isolated from the arm and thigh best maintained adipogenic potential as a function of advancing age [12].…”
Section: Donor Considerationsmentioning
confidence: 99%
“…While an analysis of breast tissues specimens from >180 women donors aged 16-73 did not observe an age dependent difference in stromal cell numbers or adipogenesis, increased body mass index correlated significantly with reduce cell numbers and differentiation [9]. Clinical studies examining subcutaneous adipose tissue from 12 to 52 donors have reported reduced ASC adipogenesis, angiogenesis, osteogenesis, and/or proliferative capacity as a function of advancing donor age [10][11][12]. Similarly, a detailed comparison of five different subcutaneous depots determined that ASC isolated from the arm and thigh best maintained adipogenic potential as a function of advancing age [12].…”
Section: Donor Considerationsmentioning
confidence: 99%
“…Most of the data regarding ADSC regenerative potential were obtained from cells delivered from relatively healthy young donors; however, it was known that aging and disease itself may negatively affect MSC activities [21][22][23][24][25][26], including proliferation and differentiation potential [27][28][29][30] as well as angiogenic properties [29,31]. Because MSCs are considered to be components of the vessel wall and take part in its reparation after injury, their cellular modification due to aging can be an important pathogenic factor of agerelated diseases such as atherosclerosis, diabetes, and arterial hypertension [32].…”
Section: Introductionmentioning
confidence: 99%
“…Adult human EPDCs were found to reduce remodelling and increase ejection fraction when transplanted into an immunodeficient mouse model of myocardial infarction [101]. Moreover, Smart et al reported that the activation of quiescent EPDCs in the adult mouse heart can be enhanced using a naturally occurring protein called thymosin beta 4 (Tβ4; a small actin-binding protein that activates integrin-linked kinase).…”
Section: Epicardium-derived Stem Cellsmentioning
confidence: 99%